Construction of Cost Effective Two Probe Device for DC Resistivity Measurement and Study the Variation of Drift Mobility of Magnetic Material with Respect to Temperature - Ravindra N. Chikhale; Vikas S. Shinde (International Journal of Scientific Research in Science and Technology, 2025)
A cost effective two probe method was constructed and used to measure dc resistivity of the given magnetic sample. The dc resistivity was measured from temperature range 303K to 773K. The activation energy of the given magnetic sample was calculated using Arrhenius relation. Resistivity and activation energy of the magnetic sample mainly depends on hopping of charge carriers between atoms. For a given magnetic sample dc resistivity found to decrease with respect to temperature became NTP type semiconductor nature of the material. The graph indicates different magnetic ordering are present in the sample at different temperatures. It is observed that Drift mobility is inversely proportional to DC resistivity and increases with increase in temperature. The DC resistivity property of materials is very important to detect applications in technology.
Keywords: Two Probe Method; Dc Resistivity; Activation Energy; Drift Mobility